The knowledge and practice of cardiopulmonary resuscitation (CPR) among nursing students - Chung, Su Chin; Clarice Duasin; Caroline Satu Jelemie; Rohani Mamat; Mazlinda Musa (Program Keperawatan, Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Surakarta, 2024)
Cardiac arrest is the sudden cessation of a person’s cardiac activity and is often fatal if corrective lifesaving interventions are not performed quickly. The American Heart Association advocates the need for high CPR competency among healthcare providers to increase the cardiac arrest survival rate. This study aimed to determine the knowledge and practice of nursing students on the acquisition and retention of CPR. A quantitative descriptive-correlation design was used, and a sample of 76 nursing students of Universiti Malaysia Sabah were recruited via a non-probability purposive technique. Data were collected using an online survey questionnaire that consists of 3 sections: Demographic, knowledge of CPR, and practice of CPR. They were analyzed using the correlation method. The results of this study are about the knowledge and practice of CPR. Nursing students' knowledge of the acquisition of CPR could be higher (39.36%), as is their practice (31.95%). The correlation coefficient between knowledge and practice is insignificant (rho = -0.073, p 0.531).In this study, both the knowledge and practice of CPR are independent.